Good luck with that - Higgins, Kristan (Berkley, 2018)
"The newest heartwarming novel from the New York Times bestselling author tells the story of two friends who make a promise to face their deepest hopes and greatest fears by agreeing to stop waiting to lose weight and start living now. Marley, Georgia, and Emerson met at fat camp as teens, and they never would have survived it without each other. They bonded against the disapproval of their family and friends by loving each other for who they were and dreaming together of when things would be better--something they formalized by writing up a list of all the things they'd do once they lost the weight... Now, seventeen years later, Emerson is morbidly obese and on her death bed from the strain of her weight on her heart. She calls Marley and Georgia to her side one last time and makes them promise her to stop waiting to live, and do the list now"--